Short Term Effect of Salt Shock on Ethylene and Polyamines Depends on Plant Salt Sensitivity - Zapata, Pedro J.; Serrano, María; García-Legaz, Manuel F.; Pretel, M. T.; Botella, M. A. (Frontiers in Plant Science, 2017)
In the present manuscript the short term effect (3-24 h) of a saline shock (NaCl 100 mM) on fresh weight, water content, respiration rate, ethylene production and Na+, Cl-, ACC and polyamine concentration was studied in four plant species with different salt sensitivity, pepper, lettuce, spinach and beetroot. Higher reduction in fresh weight and water content as a consequence of saline shock was found in pepper and lettuce plants than in spinach and beetroot, the latter behaving as more salinity tolerant. In general, salinity led to rapid increases in respiration rate, ethylene production and ACC and polyamine (putrescine, spermidine and spermine) concentrations in shoot and root. These increases were related to plant salinity sensitivity, since they were higher in the most sensitive species and vice versa. However, ethylene and respiration rates in salt stressed plants recovered similar values to controls after 24 h of treatment in salt tolerant plants, while still remaining high in the most sensitive. On the other hand, sudden increases in putrescine, spermidine and spermine concentration were higher and occurred earlier in pepper and lettuce, the most sensitive species, than in spinach and beetroot, the less sensitive ones. These increases tended to disappear after 24 h, except in lettuce. These changes would support the conclusion that ethylene and polyamine increases could be considered as a plant response to saline shock and related to the plant species sensitivity to this stress. In addition, no competition between polyamines and ethylene biosynthesis for their common precursor was observed.